EP1276 Microinvasive tubal carcinomas: cases of poor outcome despite 'very early' diagnosis. A systematic review of the literature. (1st November 2019) - Piedimonte, S; Frank, C; Laprise, C; Quaiattini, A; Gotlieb, WH
Abstract : Introduction/Background: Fortuitous cases of invasive tubal carcinoma in BRCA patients have been reported at the time of risk reducing salpingo-oophorectomy (RRSO). We performed a systematic review of the literature to determine the incidence of microinvasive tubal carcinoma in BRCA or high-risk patients undergoing RRSO, and evaluated treatment outcomes, recurrence and overall survival. Methodology: The systematic review of the literature was done using OVID, EMBASE, Medline and PubMed with keywords selected by an expert medical librarian. Two independent reviewers performed study selection, data extraction, data analysis and quality assessment. Data was extracted, recorded in a database, and synthesized using tables. Quality was assessed using an index for non-randomized studies (MINORS). Statistical analysis was done with SAS. Results: Among 2314 studies, 35 met inclusion criteria and were retained for qualitative analysis; 27 were used for quantitative analysis. A total of 6425 patients underwent RRSO between 1990 and 2019; 2963 were BRCA1 and 1605 BRCA2. Among these, 86 patients had occult tubal carcinoma. The pooled incidence of occult tubal carcinoma after RRSO in BRCA mutated or high-risk women was 1.34%, occurring at a median age of 54 years (range 42.4–67). After a median follow-up of 47.5 months, 13 recurrences and 27 cases of post-RRSO peritoneal cancer were reported. BRCA1, older age, previous breast cancer and extensive sampling of the fimbriated end were more often associated with occult malignancy. Additionally, we report a case of a 57 year old BRCA2+ patient with microinvasive tubal carcinoma found at prophylactic surgery. Despite chemotherapy and complete interval debulking, she recurred after 33 months with diffuse carcinomatosis, treated with second line calyx/carboplatin and olaparib maintenance. After 16 months, she developed acute myeloid leukaemia and died from this secondary malignancy. Conclusion: Despite early diagnosis and aggressive chemotherapy, microinvasive tubal carcinoma found at the time of RRSO can recur and result in poor outcomes Disclosure: Nothing to disclose